Identification and Phenotypic Characterization of Macrolide-Lincosamide-Streptogramin B Resistance in Streptococcus Spp. Isolates from Pharyngeal Swabs in Basra, Iraq - Mohammed, Marwan M.; Shihab, Ammar Kh.; Alsamawi, Ibrahim Ahmed Kadhim (American Journal of Biology and Natural Sciences, 2026)
Acute pharyngotonsillitis remains a widespread health concern affecting adults and children alike. Effectively treating this condition is increasingly challenged by the emergence of antibiotic-resistant bacteria, particularly among Streptococcus species. This study investigates the prevalence of these pathogens in Basra, Iraq, focusing on their resistance patterns to standard treatments, including the macrolide-lincosamide-streptogramin B (MLSB) class of antibiotics. For this purpose, throat swabs samples were collected from 270 adult patients presenting with symptoms of pharyngitis. The samples were cultured and analyzed using the Vitek system to accurately identify bacterial species and determine their antibiotic susceptibility profiles. Special attention was given to detecting MLSB phenotypes, which indicate resistance to erythromycin and clindamycin. Our findings revealed that bacterial growth was confirmed in 127 cases (47%), with a noticeably higher infection rate observed in women (59%) compared to men. The most frequently isolated pathogen was Streptococcus parasanguinis (20.5%), followed closely by Group A Streptococcus (S. pyogenes, 16.5%). Resistance testing revealed concerning trends: Streptococcus pyogenes isolates demonstrated a remarkably high resistance rate to penicillin (90.5%), deviating from global susceptibility norms. Furthermore, a constitutive MLSB resistance pattern where bacteria are resistant to both erythromycin and clindamycin was dominant across several species, including Streptococcus sanguinis and Streptococcus. orails. In conclusion, this study reveals a notable change in the region’s throat infection antibiotic resistance landscape. The prevalence of MLSB phenotypes and the unexpectedly high penicillin resistance indicate that conventional first-line treatments may not be effective, especially for those who are allergic to penicillin. In order to stop the spread of strains that are resistant to multiple drugs, it is imperative that local treatment guidelines be updated and that antibiotic use be closely monitored.